Uncorrectable coagulopathy due to intestinal obstruction: A clinical dilemma of competing priorities in a child - V Raveenthiran; S Balachandran (Wolters Kluwer Medknow Publications, 2013)
Disseminated intravascular coagulation (DIC) is a contraindication for major surgical operations. However, if surgery is required to correct the underlying cause of DIC, a clinical conflict is created. In such complex scenario, standard resources such as textbooks and journals offer very little guidance. In this communication, we report a 22-month-old boy who developed sepsis-induced DIC following intestinal obstruction. Pre-operative attempts to normalize coagulation parameters failed. Damage control laparotomy was undertaken as it was considered essential to control the underlying cause of DIC. His abnormal coagulation status reverted quickly after surgical relief of intestinal obstruction. Paradoxically intraoperative blood loss was less than anticipated amount. There are a few case reports of adult patients who have successfully undergone major surgery despite the presence of abnormal coagulation. However, this appears to be the first paediatric report of successful surgery in DIC status. Lessons learnt from this case and hypothetical speculations of clinical paradoxes are discussed.